COMPARATIVE ANALYSIS OF IDEAS IN THE KHOJAGON-NAQSHBANDIY DOCTRINE IN THE WORKS OF MUSOKHANKHOJA DAHBIDIY (Scientific journal of the Fergana State University, 2025)
This article examines the unique approaches of a prominent representative of the Naqshbandi order, Mujaddidi Musakhan Dahbidi, to the interpretation of rashahat in the Naqshbandi teachings. In his works, Dahbidi has covered in detail the issues of "sayr", "majzoob", "jazba", "dhikr" and "rashahat" in the Naqshbandi teachings. The status of pir-sheikh is also one of the aspects that the scholar pays special attention to, and he calls this level "the most perfect status".